Comparison of the Efficacy and Safety of PD‐1/PD‐L1 Inhibitors in the Treatment of Small Cell Lung Cancer - Qichen Zhang; Xiaojuan Han; Jiayi Liu; Hui Qiao (Cancer Reports)
ABSTRACT Objective This study aims to evaluate the efficacy and safety of PD‐1/PD‐L1 inhibitors in treating small‐cell lung cancer (SCLC) and determine the role of PD‐1 monoclonal antibodies in improving patient outcomes. Methods A retrospective analysis was performed on 37 SCLC patients who received PD‐1 or PD‐L1 inhibitors along with chemotherapy at the First Hospital of Lanzhou University between June 2018 and June 2023. Treatment effectiveness was measured by overall response rate (ORR), disease control rate (DCR), overall survival (OS), and progression‐free survival (PFS), utilizing chi‐square and T‐tests, along with Kaplan–Meier and log‐rank analyses. Results In the PD‐L1 group, 16 patients achieved partial or complete response, versus 12 in the PD‐1 group, though the difference in the ORR was not statistically significant (50.0% vs. 36.8%, p = 0.308). Median survival times were 21.0 months for PD‐L1 and 17.0 months for PD‐1, with no statistically meaningful difference (p = 0.180). Adverse effects were comparable between the groups in terms of thyroid function (p = 0.898), but bone marrow suppression and gastrointestinal reactions were significantly less severe in the PD‐L1 group (p = 0.047 and p = 0.002). Conclusion Immunotherapy combined with chemotherapy offers significant benefits for advanced SCLC patients, irrespective of the type of inhibitor used. Despite the higher incidence of adverse reactions with PD‐1 inhibitors, they remain a viable option, particularly when PD‐L1 inhibitors are not available, due to their manageable safety profile and effective response.